İlköğretim okullarında kullanılan formaların uyum ve kullanım özelliklerinin araştırılması - Yılmaz Akgün, Fatma (My University, 1999)
Giysiler ortamın şartlarına ve insanların o anda yaptıkları işe uygun olmalıdır. Çevre sıcaklığına ve yapılan işe uygun olarak giyinmek, insanın kendini rahat hissetmesi açısından oldukça önemlidir. Bu çalışmanın amacı; 1. Formalara yeni bir kumaş önermek, 2. Formalara yeni bir biçim kazandırmak. Bunun için tasarım kaygısı olmayan bir prototip önermek İstanbul'un ulaşım durumu düşünülerek yalnızca Kadıköy bölgesi, Kadıköy bölgesinden ise 7 okul örneklem grubu olarak seçilmiştir. Toplam 1000 öğrenci ve velinin katıldığı anket uygulaması yapılarak sonuçlar değerlendirilmiştir. Buna göre araştırmada elde edilen sonuçlar aşağıda kısaca özetlenmiştir. ? Yapılan değerlendirmeye göre ailelerin %38'i formalardan memnun, %59'u memnun değil. ? Öğrencilerin %71'i 5?6 saat forma giymek durumundadır, %13'ü 7?8 saatten daha fazla giyiyorlar. ? Öğrencilerin %68'i forma içinde kışın üşüdüklerini, %57'si yazın terlediklerini belirtir. ? Velilerin %52'si formaların 3 yıl, %27'si 2 yıl, %11'i 3 yıldan fazla dayanmasını tercih ediyor. ? Ankete göre çocukların %40'ı teneffüste, %29'u sırada otururken, %25'i tahtada yazı yazarken rahat değiller. ? Erkek öğrencilerin %41'i tuvalet öncesi pantolon toplamakta zorlanıyor. ? Öğrencilerin %60'ı kravat istemiyor. ? Bir öğrenci için okul forması tercihi %40'ına göre spor bir tarzdır. ? Araştırmada elde edilen 48. Soruya ait cevapları ise aşağıdaki gibi gruplandırılmıştır. ? Öğrencilerin fazla dar veya bol olmayan kot ve t?shirt tarzı kıyafetler istediği görülür. ? Veliler erkeklerin ve kızların birlikte kullanabileceği beli lastikli eşofman tarzı denim kumaşından üretilen formalar tercih ediliyor. ? Velilerin ciddiyet sınırları içinde denim kumaşına karşı olmadıkları görülür.

It is evident that when garments are not appropriate for the job people are doing or for the conditions of their medium; they will create a lot of inconvenience. This is the reason why dressing appropriately for the job and for the heath of the environment is so important for people since this means comfort for them. The aim of this work is to give a direction to the extreme variety presenty existing with uniforms of various primary?secondary schools, to reduce the distress this causes on the students and the parents and to help the companies producing student uniforms to get prepared before the academic year starts. The Kadikoy district of Istanbul was selected for this study due to the appparent transport problems of the city, In the Kadikoy district 7 schools were selected as a sample group. Results of a questionnaire given to a total of 1000 student and parents were evaluated. The results finally led to the preparation of a prototype school uniform. The results of the questionnaire can be summarized as follows. ? 38% of the parents are content with the uniforms while 59% are not. ? 71% of the students wear a uniform 5?6 hours/ day while 13% wear a uniform over 7?8 hours/ day. ? 68% of the students said they felt cold in their uniforms during winter while 57% said they felt hot (perspired) in their uniforms during summer. ? 52% of the parents prefer that the uniforms last longer than 3 years, while for %27 2 years is a reasonable period and for 11% the prefered lasting period for the uniforms is over 3 years. ? According to 40% of the parents their children feel uncomfortable while active during break time; according to 29% the children are uncomfortable while sitting in class and according to 25% while writing on the board. ? 49% of the female students generally felt cold most of the time since they only wore a pantyhose under their uniforms. ? 41% of the male students have difficulties in pulling up their trousers. ? 40% of the students prefer sporty type school uniforms. ? 60% of the students do not wish to wear a tie. According to the answers given to the final questions given on the questionnaire sheet the suggestions are grouped as follous. ? A uniform made of denim material which looks formal but is at the same time of sporty style is thought of as one that will reduce the discomfort to a minimum. ? It is observed that the students prefer garments that are neither too tight nor too loose and that are cot or t?shirt type. ? Trach suit style uniforms produced from denim cloth and utilizable by both sexes is prefered. ? It was observed that the parents are by no means against denim cloth as long as the uniform looks sufficiently formal.
Keywords: Eğitim; İlk öğretim; İlköğretim okulları